Restauración del monumento al General San Martín - Zanni, E.; Capdevila, J. (Revista ALCONPAT, 2011)
This work aimed to determine the causes of apparent pathological symptoms and hidden processes affecting the monument of General San Martín; as well to design the mechanisms and defining the tasks for its rehabilitation. A diagnosis was elaborated based on the following evidence: Visual inspection, metric and photographic survey and pits basements. For a better understanding, the analysis was divided into three major categories: 1. Infiltration of rainwater through the cover of the pedestal. 2. Corrosion of the metallic structural support of the sculpture. 3. Deposition and crystallization of salts on the stone base. In order to achieve complete restoration of the monument, the following steps were applied: ensuring structural stability of the sculptural group, waterproofing the cover of the pedestal, removing crystallized salts and cleaning the stone base glazes. Keywords: Pathology, Restoration, Diagnosis, corrosion of metallic structures, salt crystallization.